Cultural adaption and psychometric validation of the Danish Illness Identity Questionnaire (IIQ-DK) in adolescents and emerging adults with type 1 diabetes. Issue 3 (March 2022) - Ingersgaard, Marianne Vie; Grabowski, Dan; Olesen, Kasper
Abstract: Purpose: The Illness Identity Questionnaire (IIQ) captures the ways in which individuals integrate chronic illness into their identity. The objectives were to linguistically validate and culturally adapt a Danish language version of the IIQ, and to evaluate the psychometric properties of this Danish version. Methods: IIQ was adapted through a forward-backward translation process, content validity assessment, and cognitive interviews (n = 5). Data for psychometric analysis were collected through an online Danish version of the IIQ (IIQ-DK). Data quality, internal consistency, and item correlations were assessed. Confirmatory factor analyses (CFA) were conducted. Results: Cognitive interviews resulted in re-wordings of two items. 1176 adolescents and emerging adults (15–26 years) with type 1 diabetes completed the IIQ-DK. Floor and ceiling effects were demonstrated for most items. Analysis showed good internal consistency of scales, as well as internal and discriminant item validity. CFA fit statistics after including correlated residuals were good for all scales. CFA showed acceptably high factor loadings for all items except one. Conclusion: Results demonstrated good reliability and psychometric properties of the IIQ-DK, which may be forwarded to use in research and clinical practice as a robust instrument to measure illness identity in adolescents and emerging adults with type 1 diabetes. Abstract : Young adults; Emerging adults; Young people; Diabetes; Chronic illness; Health identity; Illness identity.